HCI International 2020 - Late Breaking Papers : User Experience Design and Case Studies : 22nd HCI International Conference, HCII 2020, Copenhagen, Denmark, July 19–24, 2020, Proceedings /: User Experience Design and Case Studies : 22nd HCI International Conference, HCII 2020, Copenhagen, Denmark, July 19–24, 2020, Proceedings. (2020) - Unknown
No abstract available